Histopathological spectrum of gallbladder lesions in cholecystectomy specimens-A Retrospective Study in a Medical College Hospital: Histopathological spectrum of gallbladder lesions in cholecystectomy specimens - Razzaque, Sabrina; Choudhury, Tamanna; Sharmin, Rizwana; Ahmad, Rahnuma; Islam, Md Ariful; Barsha, Tanzeen Parmita (Journal of the Medical College for Women & Hospital, 2025)
Background: Gallbladder disease is a common health issue and a major reason for mortality and morbidity globally. It can range from cholelithiasis, cholecystitis to various neoplastic and non-neoplastic conditions. Cholelithiasis can result in diverse histopathological alterations in the mucosa of gallbladder like inflammation (acute, chronic, granulomatous), cholesterolosis, dysplasia and malignancy. Gallbladder carcinoma are often silent clinically in its initial phase and is diagnosed commonly as incidental histological findings following cholecystectomy. Therefore, it should be a regular practice for the surgeons to send all specimens of gallbladder for histopathological examination following surgical resection of gallbladder. To exclude the possibility of gallbladder carcinoma. Aim: This study aims to analyze the histopathological alterations in specimens of surgically removed gallbladder. Materials and Method: This retrospective, hospital-based study was performed in the department of pathology of the Medical College for Women and Hospital (MCWH), Dhaka, Bangladesh, over a time period of 1 year beginning from January 2023 to December 2023 .Histopathology reports of gall bladder specimens of 251 patients who have undergone resection of gall bladder during the mentioned time frame were included in the study. The specimens received included resected gall bladders of patients diagnosed with acute or chronic cholecystitis secondary to cholelithiasis (gall stone).The information were collected from the records of histopathology reports preserved in the laboratory of MCW&H. The analysis of the data was carried out using SPSS version 26.0software (Armonk, NY: IBM Corp.) . Incomplete information or non-diagnostic samples were excluded from the study. The information was recorded in a predesigned data collection sheet. Statistical analysis was done with frequency and percentage. Results:Of the 251 cases, 42 and 209 samples were received from male and female patients, respectively. The patients’ mean age in this study was 40.92±13.19 years.Out of the various histopathological findings, the most common was chronic cholecystitis, followed by cholelithiasis (25.9%), cholesterolosis (13.5%), and acute cholecystitis (6.8%). A single case of adenocarcinoma was found. Even though premalignant conditions like intestinal metaplasia and reactive atypia was not observed, one case of xanthoglanulomatous cholecystitis (XGC) ( a potential premalignant condition)was found .Conclusion: Gallbladder diseases often require surgical intervention. Out of these, chronic cholecystitis ( a known gallbladder carcinoma risk factor), is one of the most common such disease. It is imperative to perform histopathological examination in order to detect malignant and premalignant lesions,since these may escape macroscopic detection and progress in to adenocarcinoma. J Med Coll Women Hosp.2025; 21 (2):36-46